Cynicism about Change, Work Engagement, and Job Satisfaction of Public Sector Nurses - Nguyen, D.; Teo, S.; Pick, David; Jemai, M. (Blackwell Publishing, 2018)
This paper uses the job demands-resources theory to examine the consequences of changes on nursing work. Data were collected from 220 public sector nurses in Australia to test the model. We conducted a two-wave data collection process where independent variables (organisational change, workload, job control, nursing administrative stressors, cynicism about organisational change, and demographic variables) were collected in Time 1. The dependent variables (nursing work engagement and job satisfaction) were collected 6 months later. Changes to nursing work were found to cause high workload and an increase of administrative stressors that leads to an increase in nurses’ change cynicism. Job control was needed to cope with the increase in workload and reduction in cynicism about change. Cynicism about organisational change was found to have a direct negative effect on nurses’ engagement which in turn was found to negatively impact job satisfaction. Our contribution to theory and practice arises from the discovery that the connections between organisational change, work environment variables, and job outcomes of nurses are more complicated than previous research suggests. Theoretical and practical implications will be discussed.